Ilham Allah dalam inneransi Alkitab - Suparyadi, Zakharia; Eppang, Paulus; Zebua, Yaterorogo; Saputro, Mihardo (Davar : Jurnal Teologi, 2024)
ABSTRACTThe Bible is a book of instructions and a guide for Christians that serves to teach, reveal errors, correct behavior and educate people in the truth. The Bible consists of 39 Old Testament books and 27 New Testament books which are believed to be the Word of God. The focus of this research is the development of the results of the study of the book "Vital Issues in the Inerrancy Debate" written by Geisler and based on a question: Is there really a role of God's Inspiration in the inerrancy of the Bible? And what are the functions of God's Inspiration in the inerrancy of the Bible? The purpose of this research is to produce a new study of the role of Divine Inspiration in the inerrancy of the Bible that can provide theoretical benefits. The method used in this research is qualitative, namely by studying the entire Bible, compiling information about doctrine by correlating it and trying to understand what is written, and finally seeing the culmination of Divine revelation. The results of the study of the role of God's Inspiration in the inerrancy of the Bible are as a leader, encourage and controller of the writers of the Bible. Keywords: Inspiration of God, Inerrancy, Bible. ABSTRAKAlkitab merupakan buku petunjuk dan penuntun hidup bagi orang Kristen yang berfungsi untuk mengajar, menyatakan kesalahan, memperbaiki kelakuan dan mendidik orang dalam kebenaran. Alkitab terdiri dari 39 Kitab Perjanjian Lama dan 27 Kitab Perjanjian Baru yang diyakini sebagai Firman Allah. Fokus penelitian ini merupakan pengembangan dari hasil kajian buku “Vital Issues in the Inerrancy Debate” yang ditulis oleh Geisler dan mendasarkannya pada sebuah pertanyaan: Benarkah ada peran Ilham Allah dalam inerrancy Alkitab? Dan berfungsi sebagai apa saja Ilham Allah dalam inerrancy Alkitab? Tujuan dari penelitian ini adalah menghasilkan sebuah kajian baru terhadap peranan Ilham Ilahi dalam inerrancy Alkitab yang dapat memberikan manfaat teoritis. Metode yang digunakan dalam penelitian ini adalah kualitatif, yaitu dengan mempelajari keseluruhan Alkitab, menyusun informasi tentang doktrin dengan mengkorelasikannya serta berusaha mengerti apa yang tertulis, dan akhirnya melihat kulminasi dari wahyu Ilahi. Hasil dari penelitian peranan Ilham Allah dalam inerrancy Alkitab adalah sebagai memimpin, mendorong dan pengontrol para penulis Alkitab. Kata Kunci: Ilham Allah, Ketidakbersalahan, Alkitab.